PEMBINAAN SENTRA PRODUKSI TENUN SONGKET UNGGAN OLEH PEMERINTAH KABUPATEN SIJUNJUNG - Haryani Harsari; Afrika Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Unggan Songket Weaving included one of the superior products in Sijunjung Regency its development is still not optimal. The type of research used this study is qualitative. The location of the study was conducted in Sijunjung and Sumpur Kudus Districts. The research informants used purposive sampling technique. While the data of this study are primary and secondary data. Techniques for collecting data on interviews, observation and documentation studies. Test the validity of the data in the study using source triangulation. The data analysis technique refers to the technique developed by Miles and Huberman. The results of this study indicate that the guidelines conducted by the government on Unggan weaving production centers can be seen from the role of the government that has been implemented, namely as a facilitator. regulator and catalyst. Constraints from developing the Unggan songket weaving center, namely capital, which is limited, lack of human resource management, and also weak business networks and Market Penetration Capability, and limited market access will cause products not to be marketed competitively both in the national market. and international markets. And finally, there are obstacles in the distribution and procurement of raw materials, limited access to information related to market opportunities and others.